2010
DOI: 10.1080/00102200903466210
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Coal Combustion Ashes for the Synthesis of Ordinary and Special Cements

Abstract: Raw mixes containing pulverized coal fly ash (with limestone and silica sand) or fluidized bed coal combustion ash (fly and bottom, with added limestone, anodization mud, and, when necessary, flue gas desulfurization gypsum), aimed at generating ordinary Portland or calcium sulfoaluminate clinkers, respectively, were heated in a laboratory electric oven at temperatures ranging from 1150 to 1500 C and submitted to X-ray diffraction analysis. The former had the same qualitative phase composition as that of a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Coussy 59 showed that the local crystallization stress, p c , can be related to the macroscopic stress, r * , by r * % bS c p c (7) S c in the above relationship can be calculated based on volume fraction of ettringite and total porosity of cement paste. And, p c is the local crystallization stress derived from supersaturation as shown in Eq.…”
Section: (4) Modeling Of Crystallization Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Coussy 59 showed that the local crystallization stress, p c , can be related to the macroscopic stress, r * , by r * % bS c p c (7) S c in the above relationship can be calculated based on volume fraction of ettringite and total porosity of cement paste. And, p c is the local crystallization stress derived from supersaturation as shown in Eq.…”
Section: (4) Modeling Of Crystallization Stressmentioning
confidence: 99%
“…In addition to two models described above, the crystallization stress was also estimated using poromechanics in August 2015 Expansion of OPC-CSA Blends accordance with Eq. (7). The Biot coefficient was assumed as 0.6 for cement paste 63 and S c was calculated by dividing the volume fraction of ettringite with the sum of capillary porosity and the volume fraction of ettringite.…”
Section: (4) Modeling Of Crystallization Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, low-CO 2 cements can be produced by using non-carbonated CaO sources as a constituent of the Portland clinker-generating raw mix [16,17] or increasing the production of blended cements, obtained by mixing Portland clinker with…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, any proposal aimed at employing this industrial waste should be carefully considered [1][2][3]. One of the main fields of CCA reuse is the cement and concrete industry [4] but, when this option is not economically convenient, alternative applications have to be searched for. In this context, adsorption can represent an interesting option.…”
Section: Overviewmentioning
confidence: 99%